A Case Report of 80-Year-Old Male with Total Atrioventricular Block, Acute Decompensated Heart Failure, and Non-ST-Elevation Myocardial Infarction Very High Risk: A Complicated Case in Limited Resources Setting - Wulandari, Ni Kadek Putri; Putu Sukma Parahita Aditya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Cardiovascular disease is still a major problem globally, with high morbidity and mortality rates. The progression of cardiovascular disease is so dynamic that it can leave the patient in a terminal condition. Given the high mortality and morbidity accompanied by rapid disease progression, understanding the appropriate management of each patient with comorbid heart disease is very important. Case presentation: We report an 80-year-old male with TAVB (Total Atrioventricular Block), ADHF (Acute Decompensated Heart Failure), and NSTEMI (Non-ST-Elevation Myocardial Infarction). The patient was treated and stabilized intensively in our center based on protocol. Due to the rapid progression of the disease, we referred the patient to the tertiary hospital in Bali for further advanced treatment. Conclusion: The mortality rate in cases of cardiovascular diseases is relatively high, requiring rapid and adequate treatment to provide better clinical outcomes.